Nafkah Iddah Bagi Perempuan Pasca Perceraian dalam Perundang-Undangan - Rosyida, Ryvina Izza; Maulidiyah, Dwi Faizah; Suherlan, Windy Amanda Siwi (Universitas Muhammadiyah Ponorogo, 2025)
Divorce has various legal consequences, one of which is the obligation to provide iddah maintenance for the ex-wife. Iddah maintenance is the right of divorced women during the iddah period as a form of welfare guarantee after divorce. This study aims to examine the legal provisions related to iddah maintenance in Indonesian legislation, including the Marriage Law, the Compilation of Islamic Law, and court decisions. This study is a qualitative study with a normative legal approach. Women's rights to obtain iddah maintenance after divorce are regulated in Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law. The provisions for iddah maintenance are distinguished based on the type of divorce, namely talak raj’i and talak ba’in. In talak raj’i, women have the right to receive iddah maintenance because they are still in the waiting period to remarry. Meanwhile, in talak ba’in, both in the Compilation of Islamic Law and the Law, there are no provisions that clearly regulate iddah maintenance, so women who experience talak ba’in are not automatically entitled to receive it. However, several regulations such as PERMA No. 3 of 2017 provides an affirmation regarding this matter. This study uses a normative legal approach to look at the legal provisions related to iddah maintenance, which still require clarity in protecting women.